2023
DOI: 10.1101/2023.11.10.566510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglia Depletion Reduces Human Neuronal APOE4-Driven Pathologies in a Chimeric Alzheimer’s Disease Model

Antara Rao,
Nuo Chen,
Min Joo Kim
et al.

Abstract: SUMMARYDespite strong evidence supporting the involvement of both apolipoprotein E4 (APOE4) and microglia in Alzheimer’s Disease (AD) pathogenesis, the effects of microglia on neuronal APOE4-driven AD pathogenesis remain elusive. Here, we examined such effects utilizing microglial depletion in a chimeric model with human neurons in mouse hippocampus. Specifically, we transplanted homozygous APOE4, isogenic APOE3, and APOE-knockout (APOE-KO) induced pluripotent stem cell (iPSC)-derived human neurons into the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 117 publications
0
0
0
Order By: Relevance
“…Multiple lines of evidence have shown that overexpression of APOE4 increases tau phosphorylation 16,41 and spread of tau 11,14 . Prior evidence from APOE-ε4 models shows that the activity of neuronal 42,43 , astrocytic 44 and microglial 45,46 cells increases tau pathology. Furthermore, APOE-ε4 knock in mice have displayed hyperexcitability in medial temporal regions 43,47 , a potential driver of tau accumulation 48 .…”
Section: Discussionmentioning
confidence: 97%
“…Multiple lines of evidence have shown that overexpression of APOE4 increases tau phosphorylation 16,41 and spread of tau 11,14 . Prior evidence from APOE-ε4 models shows that the activity of neuronal 42,43 , astrocytic 44 and microglial 45,46 cells increases tau pathology. Furthermore, APOE-ε4 knock in mice have displayed hyperexcitability in medial temporal regions 43,47 , a potential driver of tau accumulation 48 .…”
Section: Discussionmentioning
confidence: 97%